PEDAGOGICAL CONDITIONS FORMATION OF INTERCULTURAL COMPETENCE OF FUTURE COMBAT AND OPERATIONAL SPECIALISTS - Kukharska , Liliia; Liubas , Anzhelika (Collection of scientific papers «ΛΌГOΣ», 2023)
The article identifies and analyzes the pedagogical conditions affecting the formation of intercultural competence of future combat and operational support specialists. They include: professionalization, standardization and culturological orientation of foreign language training of future military specialists, organization of intercultural communication in the process of practical training of future combat and operational support specialists. Professionalization is considered as a special professional preparation of persons for future professional activity. Culturological direction of foreign language training implies the formation of future officers with appropriate knowledge, abilities and skills of communicative strategies, which will ensure their communication with representatives of other cultures in the process of future professional activity. Another key pedagogical condition of this process is the use of the case method and the role-playing game, which showed their effectiveness in the process of forming intercultural competence. Case method immerses future combat and operational support specialists into a problem situation and simulates conditions close to combat operations, helps to find a logical scheme for solving a certain problem. Cases help to develop such skills as practical, analytical, creative, social and communicative. The role-playing game is considered as an interactive method of training, providing simulation of professional situations and joint problem-solving activity of cadets. The role-playing game is based on the scenario consisting of communicative situations of professional direction and description of goals, tasks and roles. The above-mentioned pedagogical conditions are put in the basis of the methodology of forming intercultural competence of future specialists of combat and operational support.